2018
DOI: 10.3390/app8020183
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Pre-Treatment of Sewage Sludge in a Lab-Scale Fluidized Bed for Enhancing Its Solid Fuel Properties

Abstract: Thermal pre-treatment of non-lignocellulosic biomass, sewage sludge, using a lab-scale fluidized bed reactor was carried out in order to enhance its solid fuel properties. The influence of the torrefaction temperature range from 200-350 • C and 0-50 min residence time on the physical and chemical properties of the torrefied product was investigated. Properties of the torrefied product were analyzed on the basis of the degree of torrefaction, ultimate and proximate analysis, and gas analysis. An attempt was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…Mass loss results obtained from SS (with high initial ash content) torrefaction at 300 • C, are much greater than those obtained at lower temperatures ( Table 2). SS mass decrease ranged from 10% at 200 • C to 21% at 300 • C, which is lower than the results reported in [30,34]. Low % mass loss in this research is also lower compared with [26] where dry SS was torrefied for 50 min, and mass loss ranged from 75% to 55% for samples torrefied at 250 and 300 • C, respectively.…”
Section: Data Analysescontrasting
confidence: 77%
See 2 more Smart Citations
“…Mass loss results obtained from SS (with high initial ash content) torrefaction at 300 • C, are much greater than those obtained at lower temperatures ( Table 2). SS mass decrease ranged from 10% at 200 • C to 21% at 300 • C, which is lower than the results reported in [30,34]. Low % mass loss in this research is also lower compared with [26] where dry SS was torrefied for 50 min, and mass loss ranged from 75% to 55% for samples torrefied at 250 and 300 • C, respectively.…”
Section: Data Analysescontrasting
confidence: 77%
“…In summary, torrefaction has the potential to decompose and volatilize solids that are present in SS. Lower mass loss during torrefaction in this research compared to the results shown in [26,30] and in [40], where oxidative torrefaction was studied, could be considered as a positive outcome when evaluating fuel potential of biochar from SS. Results in this study are comparable to those reported for mass loss during torrefaction of lignocellulosic biomass (10%~30%, 1 h torrefaction) [41] depending on the type of wood used.…”
Section: Data Analysesmentioning
confidence: 51%
See 1 more Smart Citation
“…The results of the analysis are related to the specific system for which the average values of numerical parameters describing the amount and properties of sewage sludge were taken [11], [12], [14], [21], [27], [33]. Thus, the results of the analysis present a general assessment of the modified method of sewage sludge treatment, however, these may not be the same for a system with other parameters and sewage sludge with different properties than those assumed in the analysis presented in the article.…”
Section: Discussionmentioning
confidence: 99%
“…It was also assumed that the sludge concentration is 150 g/dm 3 , and anaerobic digestion efficiency is 45% [21]. The sewage sludge properties assumed for analyses were based on the results of the research presented by Karki [14] ( Table 2).…”
Section: Exergy Analysis Of Sewage Sludge Processingmentioning
confidence: 99%